2010
DOI: 10.1530/eje-09-0997
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of pituitary function in the late-postoperative phase after pituitary surgery: results of dynamic testing in patients with pituitary disease by insulin tolerance test 3 and 12 months after surgery

Abstract: The insulin tolerance test (ITT) is considered the gold standard for assessment of GH and ACTH reserve in patients with pituitary disease following pituitary surgery and is usually performed after 6-12 weeks. However, abnormal axes may not be completely recovered by then. The aim of this study was to evaluate dynamic testing 3 and 12 months after transsphenoidal pituitary surgery. Design and patients: Serial dynamic testing was performed in 36 patients (13 women, age 18-78) at 3 and 12 months after transspheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…In the further course, almost 50 % of the patients additionally experienced recovery of pituitary axes; however, loss of initially recovered functions was detected in some patients. In the context of late recovery, it was reported that dynamic re-testing at 12 months after pituitary surgery in comparison to single testing at 3 months detects a recovery from adrenocorticotropic hormone (ACTH) and growth hormone (GH) insufficiency in 11 % [10]. With respect to these results, dynamic re-testing after several months may be reasonable to avoid possibly lifelong hormone substitution therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In the further course, almost 50 % of the patients additionally experienced recovery of pituitary axes; however, loss of initially recovered functions was detected in some patients. In the context of late recovery, it was reported that dynamic re-testing at 12 months after pituitary surgery in comparison to single testing at 3 months detects a recovery from adrenocorticotropic hormone (ACTH) and growth hormone (GH) insufficiency in 11 % [10]. With respect to these results, dynamic re-testing after several months may be reasonable to avoid possibly lifelong hormone substitution therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results are hardly comparable with those in previous studies, due to different periods after surgery in which hormonal status was assessed. Hypopituitarism progressively improves after surgery (23). Arafah and Webb evaluated recovery one to six months postoperatively, unlike in our study where hypogonadism, GH deficiency, and hypothyroidism improvement were assessed on the seventh postoperative day (12,21).…”
Section: Discussionmentioning
confidence: 99%
“…63 In studies without iMRI use, the incidence of postoperative ophthalmological symptoms worsening was reported to range from 0% to 4%. 7,21,39,47 Nevertheless, due to patient and tumor characteristic variations, a direct comparison is prone to be biased.…”
Section: 21mentioning
confidence: 99%